Intestinal Spirochaetosis-A case series from the developing world. (January 2022) - Majid, Zain; Abrar, Ghazi; Ismail, Hina; Danish, Muhammad; Mubarak, Muhammad; Luck, Nasir
Spirochaetes comprise a heterogenous group of gram negative, motile, spiral shaped bacteria. Some of these pathogens are known to cause numerous human diseases such as Lyme disease, relapsing fever, syphilis and leptospirosis. However, intestinal spirochetosis is a rare condition. Patients frequently present with long-term complaints of loose stools, abdominal pain and weight loss and rectal bleeding. Hence to establish a diagnosis an endoscopy with biopsy is required. In this article, we describe four such cases, having different ages and socio- economic background, successfully treated with a short course of metronidazole.